Flow-through microscopy and image analysis for crystallization processes. (2nd February 2022) - Vancleef, Arne; Maes, Dominique; Van Gerven, Tom; Thomassen, Leen C.J.; Braeken, Leen
Highlights: Reliable and accurate particle detection algorithm for inline microscopic images. Measurements of the particle size distribution, number and solid concentration. Validation of measurements at various solid concentrations. Open source application for batch processing of images. Abstract: The particle size and particle size distribution are crucial parameters for the final product application of active pharmaceutical compounds. Image analysis with inline microscopy is an important tool for monitoring and controlling the crystallization process. This work proposes a flexible and reliable image analysis algorithm that works by combining edge detection with intensity thresholding and implementing an advanced watershed. The code is made open source and should be easily implementable. Additionally, a simple flow-through image acquisition system is developed by modifying conventional optical microscopes. Finally, measurements of the particle size, the number concentration and the solid concentration are evaluated over a wide range of solid concentrations. These can be used to measure the nucleation rate and the yield. This research should reduce the barriers towards automated image analysis and provide new methods to monitor crystallization processes.